Efektifitas penggunaan model PjBL berbantu Whatsapp Messenger terhadap Kemampuan Berfikir Kreatif Siswa Pada Kelas XI SMA Pada Mata Pelajaran Fisika - Herman Jufri Andi; Ulfatul Fitriyah; Nilna Mely Dina; Mohammad Lutfiyadi (Cetta: Jurnal Ilmu Pendidikan, 2019)
This study aims to determine the presence or absence of significant influence on the use of WhatsApp Messenger-assisted PjBL models on the creative thinking abilities of students XI SMA, and to identify the effectiveness of WhatsApp Messenger-assisted PjBL models on the creative thinking abilities of students XI SMA to direct learning model. The model used in this research is Quasi Experimental Design Nonequivalent Control Group Design. The analysis used is the normality test and homogeneity test as a prerequisite test for hypothesis testing, and the Effect Size test. Based on the data prerequisite analysis test, this research can be tested using the Independent Sample T Test because the data is normally distributed and homogeneous. Test data can be seen that the hypothesis test results with significance 0,000. Referring to the decision making decision to test the hypothesis above, H0 is rejected. So the conclusion is that there is a significant effect on the use of WhatsApp Messenger-assisted PjBL models on the creative thinking abilities of students XI SMA. While the calculation of the Effect Size test of 1,2 is in the high category with the interpretation of Cohen's value 88%.